To solve for x, we need to isolate x on one side of the equation.
First, let's subtract 40 from both sides of the equation:
-7x + 40 - 40 = -37 - 40
-7x = -77
Next, let's divide both sides of the equation by -7:
-7x / -7 = -77 / -7
x = 11
So the solution to the equation is x = 11.
solve for x.
-7x + 40 = -37
21 answers
solve for m
m/8 - 4 = -12
m/8 - 4 = -12
To solve for m, we need to isolate m on one side of the equation.
First, let's add 4 to both sides of the equation:
m/8 - 4 + 4 = -12 + 4
m/8 = -8
Next, let's multiply both sides of the equation by 8 to remove the fraction:
8 * (m/8) = -8 * 8
m = -64
So the solution to the equation is m = -64.
First, let's add 4 to both sides of the equation:
m/8 - 4 + 4 = -12 + 4
m/8 = -8
Next, let's multiply both sides of the equation by 8 to remove the fraction:
8 * (m/8) = -8 * 8
m = -64
So the solution to the equation is m = -64.
solve for x.
2/5 (10x + 15)= 26
2/5 (10x + 15)= 26
To solve for x, we need to isolate the variable on one side of the equation.
First, distribute the 2/5 to the terms inside the parentheses:
(2/5)(10x + 15) = 26
(2/5)(10x) + (2/5)(15) = 26
(4x + 6) = 26
Next, subtract 6 from both sides of the equation:
4x + 6 - 6 = 26 - 6
4x = 20
Then, divide both sides by 4 to solve for x:
4x / 4 = 20 / 4
x = 5
So the solution to the equation is x = 5.
First, distribute the 2/5 to the terms inside the parentheses:
(2/5)(10x + 15) = 26
(2/5)(10x) + (2/5)(15) = 26
(4x + 6) = 26
Next, subtract 6 from both sides of the equation:
4x + 6 - 6 = 26 - 6
4x = 20
Then, divide both sides by 4 to solve for x:
4x / 4 = 20 / 4
x = 5
So the solution to the equation is x = 5.
50(4x + 12) = -200
To solve for x, we need to isolate the variable on one side of the equation.
Let's begin by distributing 50 to the terms inside the parentheses:
50(4x + 12) = -200
200x + 600 = -200
Next, subtract 600 from both sides of the equation:
200x + 600 - 600 = -200 - 600
200x = -800
Then, divide both sides by 200 to solve for x:
200x / 200 = -800 / 200
x = -4
So the solution to the equation is x = -4.
Let's begin by distributing 50 to the terms inside the parentheses:
50(4x + 12) = -200
200x + 600 = -200
Next, subtract 600 from both sides of the equation:
200x + 600 - 600 = -200 - 600
200x = -800
Then, divide both sides by 200 to solve for x:
200x / 200 = -800 / 200
x = -4
So the solution to the equation is x = -4.
solve for x.
1.5 - x = -4.5
1.5 - x = -4.5
To solve for x, we need to isolate the variable on one side of the equation.
First, let's add x to both sides of the equation:
1.5 - x + x = -4.5 + x
1.5 = -4.5 + x
Next, let's subtract -4.5 from both sides of the equation:
1.5 - 4.5 = -4.5 + x - 4.5
-3 = x
So the solution to the equation is x = -3.
First, let's add x to both sides of the equation:
1.5 - x + x = -4.5 + x
1.5 = -4.5 + x
Next, let's subtract -4.5 from both sides of the equation:
1.5 - 4.5 = -4.5 + x - 4.5
-3 = x
So the solution to the equation is x = -3.
solve for y.
6y - 9y + 6 = -12
6y - 9y + 6 = -12
To solve for y, we need to combine like terms and isolate y on one side of the equation.
First, let's combine the y terms:
6y - 9y + 6 = -12
-3y + 6 = -12
Next, let's move the constant term to the other side of the equation:
-3y + 6 - 6 = -12 - 6
-3y = -18
Then, divide both sides by -3 to solve for y:
(-3y) / -3 = (-18) / -3
y = 6
So the solution to the equation is y = 6.
First, let's combine the y terms:
6y - 9y + 6 = -12
-3y + 6 = -12
Next, let's move the constant term to the other side of the equation:
-3y + 6 - 6 = -12 - 6
-3y = -18
Then, divide both sides by -3 to solve for y:
(-3y) / -3 = (-18) / -3
y = 6
So the solution to the equation is y = 6.
solve for w.
15w + 3w + 19 = -17
15w + 3w + 19 = -17
To solve for w, we need to combine like terms and isolate w on one side of the equation.
First, let's combine the w terms:
15w + 3w + 19 = -17
18w + 19 = -17
Next, let's move the constant term to the other side of the equation:
18w + 19 - 19 = -17 - 19
18w = -36
Then, divide both sides by 18 to solve for w:
(18w) / 18 = (-36) / 18
w = -2
So the solution to the equation is w = -2.
First, let's combine the w terms:
15w + 3w + 19 = -17
18w + 19 = -17
Next, let's move the constant term to the other side of the equation:
18w + 19 - 19 = -17 - 19
18w = -36
Then, divide both sides by 18 to solve for w:
(18w) / 18 = (-36) / 18
w = -2
So the solution to the equation is w = -2.
(6x - 10) - (2x + 12)
To simplify the expression (6x - 10) - (2x + 12), we need to distribute the negative sign to the terms inside the parentheses:
(6x - 10) - (2x + 12)
= 6x - 10 - 2x - 12 (distributing the negative sign)
= (6x - 2x) - (10 + 12) (grouping like terms)
= 4x - 22 (combining like terms)
So the simplified expression is 4x - 22.
(6x - 10) - (2x + 12)
= 6x - 10 - 2x - 12 (distributing the negative sign)
= (6x - 2x) - (10 + 12) (grouping like terms)
= 4x - 22 (combining like terms)
So the simplified expression is 4x - 22.
half the sum of a number and 26 is 15. What is the number?
Let's represent the unknown number as variable "x".
The given statement can be translated into the equation: (1/2)(x + 26) = 15.
To solve for x, we need to isolate it on one side of the equation.
First, let's multiply both sides by 2 to eliminate the fraction:
2 * (1/2)(x + 26) = 2 * 15
x + 26 = 30
Next, subtract 26 from both sides of the equation:
x + 26 - 26 = 30 - 26
x = 4
Therefore, the number is 4.
The given statement can be translated into the equation: (1/2)(x + 26) = 15.
To solve for x, we need to isolate it on one side of the equation.
First, let's multiply both sides by 2 to eliminate the fraction:
2 * (1/2)(x + 26) = 2 * 15
x + 26 = 30
Next, subtract 26 from both sides of the equation:
x + 26 - 26 = 30 - 26
x = 4
Therefore, the number is 4.
four times the difference of a number and 7 is 12. What is the number?
Let's represent the unknown number as variable "x".
The given statement can be translated into the equation: 4(x - 7) = 12.
To solve for x, we need to isolate it on one side of the equation.
First, let's distribute the 4 to the terms inside the parentheses:
4x - 28 = 12.
Next, let's move the constant term to the other side of the equation:
4x - 28 + 28 = 12 + 28.
4x = 40.
Then, divide both sides by 4 to solve for x:
4x / 4 = 40 / 4.
x = 10.
Therefore, the number is 10.
The given statement can be translated into the equation: 4(x - 7) = 12.
To solve for x, we need to isolate it on one side of the equation.
First, let's distribute the 4 to the terms inside the parentheses:
4x - 28 = 12.
Next, let's move the constant term to the other side of the equation:
4x - 28 + 28 = 12 + 28.
4x = 40.
Then, divide both sides by 4 to solve for x:
4x / 4 = 40 / 4.
x = 10.
Therefore, the number is 10.
What is the first step in solving the equation
3=6y+9
3=6y+9
The first step in solving the equation 3 = 6y + 9 is to isolate the variable on one side of the equation.
To do this, we can start by subtracting 9 from both sides of the equation:
3 - 9 = 6y + 9 - 9
This simplifies to:
-6 = 6y
So the first step in solving the equation is to subtract 9 from both sides.
To do this, we can start by subtracting 9 from both sides of the equation:
3 - 9 = 6y + 9 - 9
This simplifies to:
-6 = 6y
So the first step in solving the equation is to subtract 9 from both sides.